Handgrip Strength, Mental Health, and Quality of Life Among Older Women: Implications for AI and Big Data in Healthcare - Kim, Jae Woo; Lee, Hyo Taek (Journal of Cultural Analysis and Social Change, 2025)
Handgrip strength (HGS) is increasingly recognized as a reliable marker of muscular fitness and overall health status in older adults. This study examined the associations between HGS, mental health, and quality of life (QoL) in women aged 65 years and older, using data from the 2023 Korea National Health and Nutrition Examination Survey (KNHANES). A total of 1,742 participants with complete data on HGS, mental health, and QoL indicators were included. Low HGS, defined as <18 kg according to the Asian Working Group for Sarcopenia criteria, was observed in 48.5% of participants, with prevalence rising sharply to 65.8% among women aged 75 years or older. Multivariate logistic regression demonstrated that low HGS was significantly associated with higher odds of perceived stress (OR = 1.54), depressive symptoms (OR = 1.71), and anxiety (OR = 1.68). Furthermore, low HGS was linked to reduced EQ-5D scores, elevated HINT-8 scores, and poorer self-rated health (OR = 2.24), underscoring its multidimensional impact. These findings highlight that HGS is not merely a measure of physical performance but also a comprehensive indicator reflecting psychological well-being and QoL. Routine monitoring of HGS, integrated with IoT, artificial intelligence, and big data technologies, could serve as a practical approach for early identification and intervention in super-aged societies.